2020
DOI: 10.5007/2175-8069.2020v17n44p71
|View full text |Cite
|
Sign up to set email alerts
|

Justiça e desonestidade acadêmica: um estudo com estudantes do curso de ciências contábeis

Abstract: O propósito deste estudo foi analisar a relação entre a percepção de justiça no ambiente acadêmico e a desonestidade acadêmica de estudantes de graduação em Ciências Contábeis. A classroom justice, ou justiça acadêmica, refere-se à avaliação justa dos resultados e processos no ambiente acadêmico. É comumente segregada em três dimensões:  distributiva, processual e interacional. A amostra da pesquisa foi composta por 451 graduandos de Ciências Contábeis e os achados mostram que as três dimensões de justiça acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
0
6
0
11
Order By: Relevance
“…Through another prism, in a sample of 451 undergraduate students of accounting, Santos et al (2020) found that academic dishonesty may be a way for students to make up for perceived injustice in the educational environment. In other words, the authors concluded that, in the presence of injustice, dishonesty tends to be manifested and may be a way for students to mitigate distributive injustice (concerning the distribution of grades), procedural injustice (related to grade criteria), or interactional injustice (regarding the student-teacher relationship) in the academic environment.…”
Section: Previous Studies and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Through another prism, in a sample of 451 undergraduate students of accounting, Santos et al (2020) found that academic dishonesty may be a way for students to make up for perceived injustice in the educational environment. In other words, the authors concluded that, in the presence of injustice, dishonesty tends to be manifested and may be a way for students to mitigate distributive injustice (concerning the distribution of grades), procedural injustice (related to grade criteria), or interactional injustice (regarding the student-teacher relationship) in the academic environment.…”
Section: Previous Studies and Research Hypothesesmentioning
confidence: 99%
“…Internationally, the studies on academic dishonesty have been developed in undergraduate courses in the areas of business, including accounting (Braun & Stallworth, 2009;Bujaki et al, 2019;Johns & Strand, 2000;Kisamore et al, 2007), chemistry (Simon et al, 2004), and others (Lambert et al, 2003). In Brazil, studies on the theme are found in undergraduate courses in the areas of law, management, pedagogy, engineering (Pimenta, 2010), health (Sousa et al, 2016), accounting, and business (Avelino & Lima, 2017;Oliveira & Chacarolli, 2013;Oliveira et al, 2014;Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Os autores concluíram que o desempenho acadêmico não exerce influência na percepção de justiça em qualquer das suas três dimensões, e que a percepção de justiça do aluno está diretamente ligada ao relacionamento entre professor e aluno, e a maneira como o professor organiza o cronograma das aulas. Santos et al (2020) estudou a percepção de justiça e desonestidade acadêmica de alunos de graduação em Ciências Contábeis. A autora concluiu que as três dimensões de justiça acadêmica exercem influência sobre a desonestidade acadêmica.…”
Section: Justiça Acadêmicaunclassified
“…A terceira e última parte do questionário é composta por 34 afirmativas que compõem a escala de percepção de justiça acadêmica. Esta última parte, refere-se ao questionário utilizado por Simil (2016), Sabino et al, (2019 e Santos et al, (2020). As afirmativas 1 a 9 correspondem a percepção de justiça distributiva, as afirmativas 10 à 26 correspondem a percepção de justiça procedimental e as afirmativas 27 à 34 correspondem a percepção de justiça interacional.…”
Section: Caracterização E Instrumentos Da Pesquisaunclassified
See 1 more Smart Citation